Rape, Suicide, and the Rise of Religious Nones - Truscott, Philip (Journal of sociology and Christianity, 2024)
One of the most widely quoted concepts in late twentieth century criminology was the general theory of crime which proposed that insufficiency of self-control is the most important predictor of criminal behavior. The presence or absence of social bonds promoting self-control is an important element of this theory. This article argues that the decline of one important societal bond, religious affiliation, is impacting the incidence of rape. Since the 2010s, there has been a positive correlation between the proportion of the population declaring no religious affiliation (the "None" rate) in the 50 USA states and the campus rape rate. This correlation was significant in the four years from 2016 (r=0.464, p. 0.001) to 2019 (r=0.393, p. 0.005). Beginning in 2018, the None rate in the 50 states also correlates with the rape rate in the general US population (r=.343, p. 0.015) identified by Uniform Crime Report (UCR) data published by the Federal Bureau of Investigation. Was this due to a variation in actual crimes or in reporting rates? Recent data make the reporting rate explanation implausible. Furthermore, the UCR rape rate is directly correlated with another violence statistic that is not susceptible to reporting error: suicide rates published by the CDC. This research contends that suicide rates are a proxy indicator for male self-control, as three quarters of suicides are male. Rape perpetration is also overwhelmingly male. The correlation of rape rates and suicide rates in the USA rose from 2014 (r=.55, p. = 0.00001) to 2019 (r=.66, p. = 0.0000001). It is argued that declining religiosity is lowering self-control, and that this is a plausible mechanism driving both increased rape and suicide.